ZOOBENTHOS OF THE MIDDLE CASPIAN. BENTHOS COMMUNITIES OF THE CASPIAN SEA - S. A. Guseinova (Юг России: экология, развитие, 2014)
Abstract. Aim. Industrialization of Caspian oil and gas supplies requires a serious approach to the problem of protecting and preserving the region’s unique environment that, in fact, represents a property of international commons. The article studies into the impact of the Caspian modified waters on the benthos faunistic composition.Methods. Zooplancton and zoobenthos hydrobiology material was collected in the Central Caspian survey loop. Samples were collected in spring and summer in 2002 – 2007 in the western part of the Caspian Sea (Dagestan offshore location of the Caspian Sea from Smirnovsky Midstream Sandbank and Pearl Bank till Derbent latitude) on “Tsada” vessel. They were collected from 25 stations located on ten standard parallel latitude logs with depth scope of 8–100 m from 0, 10, 25, 100 m horizons. These samples were used as a material for characterizing phyto- and zooplankton.Results. The benthic can be considered the most stable communities of the marine environment as they are the most resilient to quantity and modifications. Heterogeneous and variable ecosystem (biotope) is typical of the areas with strong currents as the organic quality, quantity and physic-chemical properties are marked by variability.Location. The Caspian zoobenthos state as well as the features of the Caspian Sea benthos communities characterize the ecology of the Caspian Sea and give a true view of the situation in the drilling sites. This will help predict and avert negative effect of hydrocarbon production on the Caspian Sea ecosystem. Main conclusions. Water modification must be intensive, long-lasting and frequent for it to have an impact on benthos.